Enhancing Scientific Literacy of Eighth Grade Students through the Learning Model Based on Project-Based Learning and Socio-Scientific Issues - Wattanasupinyo, Nuntanut; Sangpradit, Theerapong (Science Essence Journal, 2021)
Scientific literacy is important because it helps people in making informed decisions, problem-solving in a social context related to daily life in terms of both scientific evidence and morally and ethically, in order to find the best possible solution. Therefore, the purpose of this study was to investigate the effects of the learning model based on project-based learning and socio-scientific issues on scientific literacy for eighth grade students. The samples were 40 eighth grade students in the second semester of the academic year 2020 in Bangkok and was acquired from a cluster sampling. The research design used in this study was one group pre-test post-test design; data were statistically analyzed by mean, standard deviation, percentage and t-test for dependent samples. The research instruments were 1) two lesson plans and 2) 30 questions with 10 situations scientific literacy tests. The results showed that 1) the scientific literacy mean score after the implementation was higher than those been before implementation at a statistical significance level of .05, 2) the overall level of scientific literacy changed from the low to the moderate levels. For the two sub scientific competencies, explaining phenomena scientifically and evaluating and designing scientific enquiry changed from the low to the moderate levels, 3) all students (100%) were previously in a low level of scientific literacy, but competency with a moderate or high level of evaluating and designing scientific enquiry accounts for more than 50% of total number of students and all PISA competencies exceed 50% of the total in overall after implementation.